400th Anniversary of the Visit of the Prince of Wales to Madrid, According to an Unpublished Account by Don Diego de Soto (Andamios, Revista de Investigación Social, 2026)
2023 marks the 400th anniversary of the arrival in Madrid of the Prince of Wales, Charles Stuart (1623), claiming his marriage commitment to Mary of Austria. This work brings to light D. Diego de Soto y Aguilar’s unpublished account of said visit, which, from his privileged position, reveals every detail of many festive events held in the streets and squares of the village of Madrid. This information allows us to delve deeper into the study of Madrid society in the 17th century through the artistic, social, and urban significance that these events had.
Keywords: Diego de Soto; Prince of Wales Charles Stuart; urban fabric of Madrid seventeenth century; Philip IV of Spain; bullfights